Improvement of Resistant Starch Content in Millet (Panicum miliaceum L.) Flour by Fermentation and Heat Moisture Treatment - I Desak Putu Kartika Pratiwi; Komang Ayu Nociantri (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Resistant starch is considered a valuable prebiotic source, and its content is associated not only with dietary fiber but also closely related to the amylose fraction of starch. Millet is a cereal grain rich in dietary fiber. Compared with staple cereals such as rice, wheat, and corn, millet contains higher levels of dietary fiber and antioxidants. The primary component of millet is starch, which accounts for approximately 70% of the grain, consisting of amylose and amylopectin. The research objective – to determine the best modification method to produce millet flour with the highest RS3 content. This study uses a completely randomized design with five treatment variations, repeated three times, applying different fermentation types followed by High Moisture Treatment (HMT). The analysis included the contents of starch, amylopectin, and resistant starch. The results show that significant differences in resistant starch levels were observed between treatments without HMT and those subjected to HMT. Fermentation followed by HMT effectively enhanced the resistant starch content of millet flour, highlighting the importance of combining biological and physical modifications. Among the treatments, fermentation with Lactobacillus rhamnosus SKG 34 followed by the HMT process was identified as the most effective approach, resulting in the highest resistant starch content of 3.85%. These findings demonstrate the potential of this combined modification strategy for improving the functional properties of millet flour.